The Effect of Audio Video Media on Students listening Comprehension Skill of Mts Pembangunan Nasional - Fatimah, Siti (Ability: Journal of Education and Social Analysis, 2024)
The purpose of this study was to find out the effectiveness of using songs to increase students’ listening ability in the second grade of students at the MTS Pembangunan Nasional Lubuk Pakam. The method in this research was a quasi-expeimental study, The study was carried out into two classes of research, namely experimental class and control class. The sample of this study consists of 20 students’ from VIII A class in the experimental group and 20 students’ from VIII B class in controolled group. In this study the expeimental class was taught with conventional way,The instrument used in this study was pre-test and post-test. The technique used to collect the data was quantitative with t-test. The result of this study showed that the use of media songs is effective to increase students’ listening ability. It can be seen from the result of calculation that the students’ score in experimental class was higher than control class. Bassed on stastistical calculation with the significance lavel 5%, it showed that t observation (to = 1.896) is higher than t table (tt = 1.686). it meansthere is effectiveness of using songs to increase students’ listening ability.